Chromatin immunoprecipitation microarrays for identification of genes silenced by histone H3 lysine 9 methylation - Kondo, Yutaka (National Academy of Sciences, 2004)
Switching from acetylation to methylation at histone H3 lysine 9 (K9) has recently been shown to contribute to euchromatin gene silencing. To identify genes silenced by K9 modifications, we probed a human CpG island microarray with DNA obtained by chromatin immunoprecipitation (ChIP) in a cancer cell line using an anti-H3-K9 methylated antibody or an anti-H3-K9 acetylated antibody. Of the 27 clones with the highest signal ratio of K9 methylation over acetylation (Me/Ac), 13 contained repetitive sequences. Among 14 nonrepetitive clones, we identified 11 genes (seven known and four previously undescribed), one EST, and two unknown fragments. Using ChIP-PCR, all 18 examined clones showed higher ratios of H3-K9 Me/Ac than the active gene control, P21, thus confirming the microarray data. In addition, we found a strong correlation between the K9 Me/Ac ratio and CpG island DNA methylation (R = 0.92, P < 0.01), and five of seven genes examined (megalin, thrombospondin-4, KR18, latrophilin-3, and phosphatidylinositol-3-OH kinase P101 subunit) showed lack of expression by RT-PCR and reactivation by DNA methylation and/or histone deacetylase inhibition, suggesting that these genes are true targets of silencing through histone modifications. All five genes also showed significant DNA methylation in a cell line panel and in primary colon cancers. Our data suggest that CpG island microarray coupled with ChIP can identify novel targets of gene silencing in cancer. This unbiased approach confirms the tight coupling between DNA methylation and histone modifications in cancer and could be used to probe gene silencing in nonneoplastic conditions as well.